Wide-diameter locking-taper implants: a prospective clinical study with 1 to 10-year follow-up - Mangano, C.; Luongo, F.; Mangano, F.G.; Macchi, A.; Perrotti, V.; Piattelli, A. (Journal of Osseointegration, 2014)
Aim Wide-diameter implants (WDI s, diameter ‰¥4.5 mm) are increasingly being used in patients with poor bone quality and reduced bone height. The aim of this study was to evaluate the survival rate, peri-implant bone loss, biological and prosthetic complications of wide-diameter (4.8 mm) lockingtaper implants used in the restoration of partially and fully edentulous patients. Materials and methods Between January 2002 and December 2011, all patients referred to a private clinic for treatment with WDI s were considered for inclusion in the study. At each annual follow-up session, clinical and radiographic parameters were assessed: the outcome measurements were implant failure, peri-implant bone loss (distance between the implant shoulder and the first visible bone-to-implant contact: DI B), biological and prosthetic complications. The cumulative survival rate (CSR ) was assessed using the Kaplan- Meier estimator; Log-rank was applied to evaluate correlations between the study variables. The statistical analysis was performed at the patient and at the implant level. Results A total of 438 WDI s were placed in 411 patients. Four implants failed, for a CSR of 99% (patient-based) and 99.1% (implant-based) at 10-year follow-up. The CSR did not differ significantly with respect to patients€™ gender, age, smoking or parafunctional habit, implant location, position, length, bone type or prosthetic restoration. A mean DI B of 0.34 mm (± 0.23), 0.45 mm (± 0.27) and 0.75 mm (± 0.33) was shown at the 1-, 5- and 10-year follow-up examination. Conclusions Wide-diameter, locking-taper implants can be a good treatment option for the rehabilitation of partially and fully edentulous patients over the long term.